(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article analyzes the content and forms of developing students’ socio-cultural competence in education. The development of students’ socio-cultural competencies requires vital conditions. The ongoing processes of globalization and the consequent integration of cultural, social, economic and political relations between countries, regions and peoples increase the need for the development of cultural competencies of students and future professionals.